Bis(N-sec-butyl-N-n-propyldithiocarbamato- 2S,S')(1,10-phenanthroline- 2N,N')zinc(II) - Alzaalouk, Amna Salem; Baba, Ibrahim; Mohamed Tahir, Mohamed Ibrahim; Ng, Seik Weng; Tiekink, Edward Richard Tom (International Union of Crystallography, 2010)
Two independent but very similar mol-ecules comprise the asymmetric unit of the title compound, [Zn(C(8)H(16)NS(2))(2)(C(12)H(8)N(2))]. The N(2)S(4) donor set about Zn is defined by two symmetrically chelating dithio-carbamate ligands and a 1,10-phenanthroline ligand. Distortions from the ideal octa-hedral coordination geometry arise from the restricted bite angles of the ligands. The main feature of the crystal packing is the formation of tetra-meric supra-molecular aggregates mediated by C-H⋯S inter-actions. Disorder was found in each of the sec-butyl groups. This was resolved over two positions in each case with the major components of the disorder having site occupancies in the range 0.551 (6)-0.725 (5).